A phenomenological computational model of the evoked action potential fitted to human cochlear implant responses - Ramos-de-Miguel, Ángel; Escobar, José M.; Greiner, David; Benítez, Domingo; Rodríguez, Eduardo; Oliver, Albert; Hernández, Marcos; Ramos-Macías, Ángel (PLOS Computational Biology, 2022)
Author summary The cochlea, found in the inner ear, is the organ where the sound is transformed into an electrical pulse to be transmitted by the neurons to the auditory cortex. Hearing loss can be caused by damage to the hair cells, in which case neuronal excitation is impaired. CIs are devices that replace the normal function of the impaired/damaged Organ of Corti. Computational models allow a better understanding of the mechanisms involved in the electrical stimulation of the auditory nerve. These models can help biomedical engineers to develop new CIs with improved auditory performance. One important aspect of our model is its customization with the patient’s data provided by the recording of the evoked compound action potential (the synchronous firing of a population of electrically stimulated auditory nerve fibers). This phenomenological model allows us to predict the registers of neural stimulation produced when the auditory nerve is stimulated with the CIs. We have validated the proposed model with real data obtained from two patients with CIs.